Structural similarities among significant others and acquaintances measurable?.[article]. - Dans-Lopez, Gilda
This study employs a variation of Kelly's Repertory grid, called the Star matrix, as a model to depict objects and structures in individual consciousness. It uses numbers as symbolic portrayals of figure representations in psychological space, and then explores whether a computation of similarity among these representations reasonably reflects the structures in mental life. Participants were 66 adolescents. Q correlation was used to measure structural similarities among significant others and acquaintances. this was compared to participants' rank-ordering of acquaintances according to perceived similarity with a significant other. using idiographic-nomothetic methods, It was found that there was a fair convergence of the participants, essays further showed that the structural measure was meaningful to a subject when congruence was high between the Q and participants' perception.